Generalized Levitin-Polyak Well-Posedness of Vector Equilibrium Problems. (22nd November 2009) - Peng, Jian-Wen; Wang, Yan; Zhao, Lai-Jun
Abstract : We study generalized Levitin-Polyak well-posedness of vector equilibrium problems with functional constraints as well as an abstract set constraint. We will introduce several types of generalized Levitin-Polyak well-posedness of vector equilibrium problems and give various criteria and characterizations for these types of generalized Levitin-Polyak well-posedness.